2016
DOI: 10.1007/s12160-016-9833-5
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Risk of Frailty: the English Longitudinal Study of Ageing

Abstract: BackgroundThere is evidence that the personality traits conscientiousness, extraversion and neuroticism are associated with health behaviours and with risk of various health outcomes. We hypothesised that people who are lower in conscientiousness or extraversion or higher in neuroticism may be at greater risk of frailty in later life.MethodsWe used general linear models to examine the prospective relation between personality, assessed using the Midlife Development Inventory, and change in frailty, modelled by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 59 publications
(63 reference statements)
6
25
0
Order By: Relevance
“…Overall, the results of the phenotypic analyses are in line with previous studies examining the association between neuroticism and frailty, using both measures of physical frailty (i.e. the frailty phenotype) and the frailty index (10)(11)(12). Our study expanded the follow-up time up to 29 years, elucidating the stability of neuroticism in midlife as a predictor of late life frailty.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Overall, the results of the phenotypic analyses are in line with previous studies examining the association between neuroticism and frailty, using both measures of physical frailty (i.e. the frailty phenotype) and the frailty index (10)(11)(12). Our study expanded the follow-up time up to 29 years, elucidating the stability of neuroticism in midlife as a predictor of late life frailty.…”
Section: Discussionsupporting
confidence: 85%
“…depressed mood, worry, fear), has been consistently associated with a wide range of physical and mental health problems such as cardiovascular disease, disrupted immune functioning, asthma, irritable bowel syndrome, atopic eczema, migraine, mood and anxiety disorders, and even increased risk of premature mortality (7)(8)(9), potentially also affecting frailty. The association between neuroticism and frailty has been investigated in three previous studies, all suggesting that high neuroticism is associated with higher frailty concurrently and longitudinally, over up to eight years (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, people who are higher in neuroticism, the tendency to experience negative emotion, may have an increased risk of cognitive decline [ 107 ] and dementia [ 108 ]. In a prospective study of people aged 60 to over 90 years, higher levels of neuroticism and lower levels of extraversion and conscientiousness were associated with greater frailty at follow-up around 2 years later [ 109 ]. There is evidence that personality may be associated with individual differences in physiological processes that have been hypothesized to underlie the onset of frailty, namely inflammation and the HPA dysregulation [ 110, 111 ].…”
Section: Possible Neurobiological Mechanisms Underlying Cognitive Framentioning
confidence: 99%
“…This critique focuses, inter alia, on its failure to take into account the role played in precipitating frailty by domains outside the biological, including social disadvantage [3]; its overlooking of positive aspects of frail embodiment/resilience [4]; its incorporation of psycho-social aspects in a dualistic framework that posits the separation of mind and body [5]; its perpetuation of decline narratives; and ultimately its potentially (albeit unintentionally) harmful impact on older people who are labelled 'frail', which may in turn trigger frailty identity crises [6] precipitating a 'cycle of decline' [7]. The importance of subjectivity is also highlighted in clinical literature: for example, negative representations of ageing may underpin a decline in objective walking speed [8]; in addition, the English Longitudinal Study of Ageing suggested that older people who have a more positive attitude to ageing may be at reduced risk of becoming physically frail or pre-frail [9].…”
Section: The Disjunction Between Clinical Approaches and Lived Experimentioning
confidence: 99%